Arguing for a conscious emergence of language - Cardini, Filippo-Enrico (Lingua, 2017)
•I evaluate a possible example of spontaneous emergence of language.•I argue that language was the product of human inventions.•Inventions were enabled by a new level of awareness and a new representational system.•Language is not syntactocentric. In the present article it is argued that the first instances of linguistic communication between early humans were characterised by the use of consciously invented signs. This position is in contrast with what is probably the mainstream view on the subject, which holds that language is the result of a biologically acquired communicative ability that spontaneously, instinctively, began to manifest itself in the mouths or hands of the very first language users. By highlighting the inextricable link existing between linguistic production and conscious thought, I claim that the first true linguistic items that appeared on the evolutionary scene could never have been generated had a higher level of consciousness not come to characterise the human mind, enabling it to perform ‘thinking about thinking’. Key to this novel mental capacity was the acquisition of a new type of representational system accessible to conscious awareness. The view of language emergence suggested here inevitably clashes against some important theories about language and its evolution. By placing conscious meaning right at its core, it rejects, for example, syntatctocentric approaches to language. It also distances itself from accounts of language evolution which predict linguistic forms to have arisen before linguistic meanings.